Informative discourse and migration. Analysis of televisionproduction routines and sociocultural diversity in Andalusia - González Cortés, María Eugenia; Sierra Caballero, Francisco; Benítez Eyzaguirre, Lucía (Estudios sobre el Mensaje Periodístico, 2014)
Limitations and daily routine of press activity are aspects that are usually put away when we speak about the approach to the diversity within the media, but, on the other hand, they have great importance when it comes to build an imaginary and in the multimodal discourses about migration. Using the analysis of Canal Sur Televisión´s news together with the interviews to professional workers of the media, it´s been studied the way to build, speaking about the media world, the diversity in this regional public channel, attending to the boundaries established by: press criteria, making professional decisions, influence of social and politics discourses and the observance of the Style Guide. As methodological tools, analysis of contents and indepth interviews to journalists and cameramen from Málaga, Cádiz, Almería, Algeciras y Granada are combined, a total of sixteen.